Governing process of building association in contemporary Vietnam - Thuong, Huyen Le (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
The right to form associations is a human right recognized in many international political and legal documents. In countries led by a single party, the formation of associations can influence issues related to human rights and conflict with national management interests. In this context, this article examines the legal aspects related to the right to form associations in Vietnam today. This research aims to collect, analyze, and clarify aspects of the right to form associations in Vietnam. It assesses the current legal status of the implementation of the right to form associations in Vietnam. The research method used in this article is a literature review. The results of the research show that Vietnam has nearly 70,000 associations, including more than 1,200 international non-governmental organizations. Associations and organizations cover various issues such as the environment, social security, scientific research, ethnic minorities, water resource management, and forests. Although the formation and operation of associations still face many difficulties and obstacles, the role of associations is to coordinate and jointly resolve complex, urgent, and emerging social issues with state management institutions. This article discusses governance issues related to the formation of associations since Doi Moi (1986).